Radiation exposure to eye lens and operator hands during endovascular procedures in hybrid operating rooms - Attigah, Nicolas; Oikonomou, Kyriakos; Hinz, Ulf; Knoch, Thomas; Demirel, Serdar; Verhoeven, Eric L. G.; Böckler, Dittmar (Journal of vascular surgery, 2016)
Objective - The purpose of this study was to evaluate the radiation exposure of vascular surgeons' eye lens and fingers during complex endovascular procedures in modern hybrid operating rooms. - Methods - Prospective, nonrandomized multicenter study design. One hundred seventy-one consecutive patients (138 male; median age, 72.5 years [interquartile range, 65-77 years]) underwent an endovascular procedure in a hybrid operating room between March 2012 and July 2013 in two vascular centers. The dose-area product (DAP), fluoroscopy time, operating time, and amount of contrast dye were registered prospectively. For radiation dose recordings, single-use dosimeters were attached at eye level and to the ring finger of the hand next to the radiation field of the operator for each endovascular procedure. Dose recordings were evaluated by an independent institution. Before the study, precursory investigations were obtained to simulate the radiation dose to eye lens and fingers with an Alderson phantome (RSD, Long Beach, Calif). - Results - Interventions were classified into six treatment categories: endovascular repair of infrarenal abdominal aneurysm (n = 65), thoracic endovascular aortic repair (n = 32), branched endovascular aortic repair for thoracoabdominal aneurysms (n = 17), fenestrated endovascular aortic repair for complex abdominal aortic aneurysm, (n = 25), iliac branched device (n = 8), and peripheral interventions (n = 24). There was a significant correlation in DAP between both lens (P < .01; r = 0.55) and finger (P < .01; r = 0.56) doses. The estimated fluoroscopy time to reach a radiation threshold of 20 mSv/y was 1404.10 minutes (90% confidence limit, 1160, 1650 minutes). According to correlation of the lens dose with the DAP an estimated cumulative DAP of 932,000 mGy/m2 (90% confidence limit, 822,000, 1,039,000) would be critical for a threshold of 20 mSv/y for the eyes. - Conclusions - Radiation protection is a serious issue for vascular surgeons because most complex endovascular procedures are delivering measurable radiation to the eyes. With the correlation of the DAP obtained in standard endovascular procedures a critical threshold of 20 mSv/y to the eyes can be predicted and thus an estimate of a potential harmful exposure to the eyes can be obtained.